Response to Intervention: Instructional Challenges for Teachers in High Need Contexts. Issue 9 (September 2017) - Nichols, Sharon L.; Castro-Villarreal, Felicia; Ramirez, Amanda
Background: This study adds to our understanding of how elementary school teachers in culturally and linguistically diverse contexts think about the implementation and impact of Response-to-Intervention practices. Purpose of Study: The purpose of this study is to understand elementary school teachers' beliefs about the challenges associated with RTI implementation with high need, high risk student populations. Research Design: This was a semi-structured interview study with eight elementary school teachers. Findings/Results: Interview data indicate that while teachers noted the potential of RTI systems and processes, most expressed dissatisfaction with implementation variability, inadequate training, slow matriculation through the tiers, and widely diverse student learning needs. Teachers also noted challenges associated with having to differentiate instruction and management with widely diverse learners while at the same time being pressured to meet accountability targets. Conclusions: We conclude that although RTI has become more widely understood and recognized, there remain serious implementation challenges and confusion in contexts that serve culturally and linguistically diverse students. We recommend improved training at the university and preservice level to prepare teachers for work in tiered problem-solving frameworks and to help teachers better understand the academic, social, and affective needs of our increasingly diverse student population.